The Determinants and Economic Effects of Defence Spending: The Case of Rwanda, 1973-2020 - Rossmeisl, Daniel P (School of Economics, 2025)
There is a long and established literature – both theoretical and empirical – regarding the effects that a country's defence burden has on its growth prospects. However, the results remain inconclusive. Fewer studies consider the determinants of a government's defence spending decision, and many of these studies restrict their analysis to groups of countries, thus, failing to capture significant, country-specific features. Considering the high, and rising, instances of security concerns on the African continent, there is an imperative for economists to understand the demand and supply aspects of military spending by African governments. This dissertation advances the existing literature by providing empirical evidence on both the demand and supply issues affecting defence spending by focusing on Rwanda; an African country that is one of the continent's fastest growing economies, a significant trading partner with both Eastern and Western blocs, and a regional power that has experienced multiple conflicts over the past five decades. Employing the Autoregressive Distributed Lag (ARDL) approach to cointegration for the period 1973-2020, the study finds compelling evidence confirming the growth retarding effects of defence spending while also demonstrating that conflict and economic factors have been key determinants of the country's level of military expenditure. These findings are very important for policy makers that aim to facilitate the country's development processes – especially in a postconflict era